Business Processes Administration at a Construction Enterprise - Bakalo, Nadiya; Hunchenko, Mariya; Makhovka, Viktoriia (International Journal of Engineering and Technology, 2018)
The article deals with the theoretical essence and meaning of the term "administration". The administration of construction enterprises is considered from the viewpoint of the process approach and focused on business processes that are described, regulated, are constantly monitored and subject to adjustments in case of implementation errors detection or deviations from the results. The authors distinguish two approaches to the administration of business processes, which are advisable to use at construction enterprises: improving existing business processes and their reengineering.Â Â